Los test motrices para el diagnóstico del desarrollo de la psicomotricidad fina - Chulco Tisalema, Daniela Cecilia (2023)
In this research, the importance of the psychomotor tests use was diagnosed, which allow to determine the development level of the students’ fine psychomotor skills, with the purpose of evidencing the shortcomings in the psychomotor children development, considering that the Lack of psychomotor stimulation can cause permanent and irreversible consequences in the children psychomotor and intellectual skills development. In fact, this research "Motor tests for the development diagnosis of fine psychomotor " was carried out, the same one that had with the objective of diagnosing the fine motor skills development through the application of motor tests at children from Initial Education. The methodological design of this research was framed in the qualitative approach, oriented towards a field and bibliographical investigation of a descriptive nature with the inductive method use that allowed the theoretical framework working out. The techniques used in the investigation were the interview, which was applied to the teachers, as well as an observation sheet for the students, obtaining direct and valid information on the current situation of fine motor skills development in children. Being a theoretically supported study, becomes a starting point for new research that is interested in knowing about the different types of tests or motor tests that diagnose the evolution from existing psychomotor development.